A Robust, Water‐Based, Functional Binder Framework for High‐Energy Lithium–Sulfur Batteries. Issue 13 (9th June 2017) - Lacey, Matthew J.; Österlund, Viking; Bergfelt, Andreas; Jeschull, Fabian; Bowden, Tim; Brandell, Daniel
Abstract: We report here a water‐based functional binder framework for the lithium–sulfur battery systems, based on the general combination of a polyether and an amide‐containing polymer. These binders are applied to positive electrodes optimised towards high‐energy electrochemical performance based only on commercially available materials. Electrodes with up to 4 mAh cm −2 capacity and 97–98 % coulombic efficiency are achievable in electrodes with a 65 % total sulfur content and a poly(ethylene oxide):poly(vinylpyrrolidone) (PEO:PVP) binder system. Exchange of either binder component for a different polymer with similar functionality preserves the high capacity and coulombic efficiency. The improvement in coulombic efficiency from the inclusion of the coordinating amide group was also observed in electrodes where pyrrolidone moieties were covalently grafted to the carbon black, indicating the role of this functionality in facilitating polysulfide adsorption to the electrode surface. The mechanical properties of the electrodes appear not to significantly influence sulfur utilisation or coulombic efficiency in the short term but rather determine retention of these properties over extended cycling. These results demonstrate the robustness of this very straightforward approach, as well as the considerable scope for designing binder materials with targeted properties. Abstract : Function over form : functional binders based on a general combination of polyether‐ and amide‐containing polymers enable high‐capacity electrodes for lithium–sulfur batteries using only commercially available materials and a simple water‐based preparation procedure.